Achieving λ/10 Resolution CW STED Nanoscopy with a Ti:Sapphire Oscillator - Liu, Yujia (Public Library of Science, 2012)
In this report, a Ti:Sapphire oscillator was utilized to realize synchronization-free stimulated emission depletion (STED) microscopy. With pump power of 4.6 W and sample irradiance of 310 mW, we achieved super-resolution as high as 71 nm. With synchronization-free STED, we imaged 200 nm nanospheres as well as all three cytoskeletal elements (microtubules, intermediate filaments, and actin filaments), clearly demonstrating the resolving power of synchronization-free STED over conventional diffraction limited imaging. It also allowed us to discover that, Dylight 650, exhibits improved performance over ATTO647N, a fluorophore frequently used in STED. Furthermore, we applied synchronization-free STED to image fluorescently-labeled intracellular viral RNA granules, which otherwise cannot be differentiated by confocal microscopy. Thanks to the widely available Ti:Sapphire oscillators in multiphoton imaging system, this work suggests easier access to setup super-resolution microscope via the synchronization-free STED.